NCMP-09. ISOCITRATE DEHYDROGENASE MUTATIONS AND INCREASED TISSUE 2-HYDROXYGLUTARATE CONCENTRATION MIGHT BE RELATED WITH SEIZURE ONSET IN PATIENTS WITH GLIOMAS. (5th November 2018) - Ohno, Makoto; Hayashi, Mitsuhiro; Matsushita, Yuko; Miyakita, Yasuji; Takahashi, Masamichi; Yamazawa, Erika; Tsushita, Natsuko; Ichimura, Koichi; Hamada, Akinobu; Narita, Yoshitaka
Abstract: Mutations in isocitrate dehydrogenase 1 or 2 genes (IDH1/2) frequently occur in lower-grade gliomas and secondary glioblastomas. Mutant IDH1/2 proteins gain a new ability to produce the oncometabolite 2-hydroxyglutarate (2HG). Recently, IDH1/2 mutations were suggested to be related with seizure onset through the structural similarity of 2HG to the excitatory neurotransmitter glutamate. Therefore, we sought to investigate the relationship between seizure onset and IDH1/2 status, tissue 2HG concentration and distribution. We assessed 149 patients with WHO grade II-IV glioma, whose IDH1/2 status were identified and measured serum and tissue 2HG concentrations in 123 and 104 patients by using liquid chromatography-tandem mass spectrometry method. The matrix assisted laser desorption and ionization mass spectrometry imaging (MALDI-MSI) was use to analyze tissue 2HG distribution for 12 tissue samples. Seizure onset was observed in 34 among 56 (60.7%) patients with IDH mutant tumor, whereas in 18 among 93 (19.4%) patients with IDH wild-type tumor (p<0.0001). The median tissue 2HG concentrations in patients with seizure onset were significantly higher than in those without seizure onset (2860mg/mg vs 110mg/mg, p<0.0001). Receiver operating characteristic analysis suggested the cutoff value of the tissue 2HG concentration was of 1190mg/mg. Multivariate analysis, including tissue 2HG concentration, serum 2HG concentration, IDH1/2 mutation, tumor histology, WHO grade, tumor location, and patient age, suggested that tissue 2HG concentration and serum 2HG concentration were significantly correlated with seizure onset. The MALDI-MSI showed heterogeneous 2HG distribution in IDH mutant sections. Our results suggest that increased tissue 2HG concentration and heterogeneous distribution might be related to seizure onset in patients with gliomas.